Entrepreneurship in the EU : to wish and not to be - Isabel Grilo; Jesús Maria Irigoyen (Max Planck Institute for Research into Economic Systems, 2005)
It is now widely acknowledged that the entrepreneurial capacity in an economy is a key determinant of economic growth and productivity improvements. This paper uses survey data from the 15 EU Member States and the US to establish the effect of demographic and other variables on latent and actual entrepreneurship. Latent entrepreneurship is measured by the probability of a declared preference for self-employment over employment. Other than demographic variables such as gender, age and education level, the set of explanatory variables used includes country specific effects, the perception by respondents of administrative complexities and of availability of financial support and a rough measure of risk tolerance. The most striking result is the lack of explanatory power of the perception of lack of available financial support in the latent entrepreneurship equation.
More recent version: http://hdl.handle.net/10419/110992
Keywords: R12; J23; M13; 330; Entrepreneurship; self-employment; administrative complexities; access to finance; risk attitudes; probit regression; Unternehmer; Unternehmensgründung; Schätzung; Bürokratie; Risikopräferenz; Finanzierung; EU-Staaten